The Effect of Magnetic Field with Nanofluid on Heat Transfer in a Horizontal Pipe - Karamallah, Abdulhassan A.; Habeeb, Laith Jaafer; Asker, Ali Habeeb (Al-Khwarizmi Engineering Journal, 2017)
This work presents an experimental study of heat transfer and flow of distilled water and metal oxide nanofluid Fe3O4-distilled water at concentrations of (φ = 0.3, 0.6, 0.9 %) by volume in a horizontal pipe with constant magnetic field. All the tests are carried out with Reynolds number range (2900-9820) and uniform heat flux (11262-19562 W/m2). The results show that, the nanofluid concentration and magnetic intensity increase, the Nusselt number increases. The maximum enhancement in Nusselt number with magnetic nanofluid is (5.4 %, 26.4 %, 42.7 %) for volume concentration (0.3, 0.6, 0.9 %) respectively. The enhancement is maximized with magnetic intensity (0.1, 0.2, 0.3 tesla) respectively to (43.9, 44.3, 46 %) with volume concentration (0.9 %). The heat transfer enhancement decreases with the increasing of Reynold number with using magnets. The friction factor increases with nano volume concentration increase and the intensity of magnet and decreases with increase of Reynold number.